Pure erythroid leukemia in a polymyositis patient treated with azathioprine - Imataki, Osamu (Rare Tumors, 2018)
Acute erythroid leukemia, also known as acute myeloid leukemia-M6, may be associated with previous chemotherapy or immunosuppressive therapy. For 10 years, a 69-year-old Japanese female patient with pure erythroid leukemia (or acute myeloid leukemia-M6b) was treated for polymyositis with 50–100 mg/day azathioprine. She complained of dyspnea with low-grade fever and was diagnosed as having pure erythroid leukemia. Chromosomal analysis revealed a complex karyotype abnormality, with the deletion of 5q, -6, -7 and addition of 11q13. No morphological myelodysplastic changes were observed in her bone marrow cells. In this study, azathioprine accumulation was considered to be associated with the patient’s leukemogenesis.